The effectiveness of the use lecture journal books in improving learning outcome of PGSD student's - Mohammad Archi Maulyda; Radiusman Radiusman; Muhammad Erfan; Darmiany Darmiany; Asrin Asrin (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2020)
Student lecture journals are a form of development of notebooks that are commonly used by elementary, middle and high school students. Lecture journals contain a summary of lectures in one day and are made more systematically accompanied by a clear format. But the use of lecture journals at the tertiary level is still very low. Therefore, the purpose of this study is to see whether the use of lecture journals can improve student learning outcomes. The type of research chosen is quantitative to see the significance of the use of the control class and the experimental class. Data will be tested using t-independent test. T test results show that lecture journals can influence student learning outcomes. To see the enhancements used the formula test-gain / normalized gain. Based on the results of the calculation of the gain-test / normalized gain it can be seen that there is an increase in student learning outcomes for the experimental class using lecture journals in learning by 22.67%. Whereas students who did not use lecture journals increased learning outcomes by only 14.6%. This shows that student learning outcomes can be improved if students use lecture journals in the learning process